2020
DOI: 10.1136/bmjopen-2019-035045
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic models for predicting in-hospital paediatric mortality in resource-limited countries: a systematic review

Abstract: ObjectivesTo identify and appraise the methodological rigour of multivariable prognostic models predicting in-hospital paediatric mortality in low-income and middle-income countries (LMICs).DesignSystematic review of peer-reviewed journals.Data sourcesMEDLINE, CINAHL, Google Scholar and Web of Science electronic databases since inception to August 2019.Eligibility criteriaWe included model development studies predicting in-hospital paediatric mortality in LMIC.Data extraction and synthesisThis systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…A recent systematic review by Ogero et al identified 21 models predicting in-hospital pediatric mortality in LMICs [ 37 ]. Of note, all these 21 models used clinical signs on admission, while none used daily clinical data to predict outcomes later during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review by Ogero et al identified 21 models predicting in-hospital pediatric mortality in LMICs [ 37 ]. Of note, all these 21 models used clinical signs on admission, while none used daily clinical data to predict outcomes later during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Most models had several important methodological concerns, such as a priori selection of predictors and ignoring censoring with the use of logistic models. Some models require monitoring of vital signs or laboratory measurements, which pose difficulties to implementation [ 37 ]. Therefore, the present study is unique in its inclusion of daily clinical parameters (not selected beforehand) capturing disease dynamics throughout hospitalization in predicting in-patient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These risk scores have not been widely validated using data from low- and middle-income settings outside sub-Saharan Africa [ 8 , 9 ]. The RISC score for HIV-negative children had fair discriminatory value when retrospectively applied to the PERCH and RISC-Malawi data sets, both of which were done after the pneumococcal vaccine became available and large scale prevention of mother to child transmission of HIV implementation [ 6 , 7 ].…”
mentioning
confidence: 99%
“…Implementation of FASTER monitoring with sufficient caregiver education on goals to hasten interventions and without the label of a red flag may help address this issue. Given recent data on mortality predictions scores improving by including at least one element of the four top categories of altered consciousness, vital signs, signs of respiratory distress and indicators of malnutrition, addition of mid-upper arm circumference is important to consider to increase sensitivity and specificity of the FASTER tool ( 20 ).…”
Section: Discussionmentioning
confidence: 99%